Reader Response Journals in The Analysis of Literary Works among Undergraduate Students - Revathi Gopal; Theresa Eng May Lee (English Education Journal, 2023)
This study aims to investigate the effectiveness of reader response journals in the analysis of literary works among Malaysian TESL undergraduate students. The study employs mixed method approach and addresses a research question, ‘What are Malaysian TESL undergraduate students’ perceptions on the use of reader response journals in the analysis of literary works?’ Six students of moderate competency in the English language were selected for an interview session to investigate participants’ perceptions of the reader response journals in poem analysis. Interview data were analysed by using thematic analysis in identifying the emerging themes. The findings revealed an increase in aesthetic stance in students’ literary analysis. Besides, students shared that their analyses were more critical with the help of reader response journals. This study proposes an alternative method and strategy to learn literature aesthetically.